Pleuromutilins: use in food-producing animals in the European Union, development of resistance and impact on human and animal health. (3rd May 2014) - van Duijkeren, Engeline; Greko, Christina; Pringle, Märit; Baptiste, Keith Edward; Catry, Boudewijn; Jukes, Helen; Moreno, Miguel A.; Pomba, M. Constança Matias Ferreira; Pyörälä, Satu; Rantala, Merja; Ružauskas, Modestas; Sanders, Pascal; et al.
Abstract : Pleuromutilins (tiamulin and valnemulin) are antimicrobial agents that are used mainly in veterinary medicine, especially for swine and to a lesser extent for poultry and rabbits. In pigs, tiamulin and valnemulin are used to treat swine dysentery, spirochaete-associated diarrhoea, porcine proliferative enteropathy, enzootic pneumonia and other infections where Mycoplasma is involved. There are concerns about the reported increases in the MICs of tiamulin and valnemulin for porcine Brachyspira hyodysenteriae isolates from different European countries, as only a limited number of antimicrobials are available for the treatment of swine dysentery where resistance to these antimicrobials is already common and widespread. The loss of pleuromutilins as effective tools to treat swine dysentery because of further increases in resistance or as a consequence of restrictions would present a considerable threat to pig health, welfare and productivity. In humans, only one product containing pleuromutilins (retapamulin) is authorized currently for topical use; however, products for oral and intravenous administration to humans with serious multidrug-resistant skin infections and respiratory infections, including those caused by methicillin-resistant Staphylococcus aureus (MRSA), are being developed. The objective of this review is to summarize the current knowledge on the usage of pleuromutilins, resistance development and the potential impact of this resistance on animal and human health.